Creating Local Icon through Traditional Opera: Suroloyo Dance Fragment in Kulon Progo and Canggeuk in Seoul - Hasanah, Ummul; Asrori, Yuni Wachid; Shalsabilla, Niken Oktavia (Humanus, 2024)
Recently, many regional areas have been trying to quantify the number of tourists visiting their regions. It is because the tourism sector has so many good impacts, not only economic impacts but also the sociocultural development of those in that area. One of the ways to be seen as unique by foreigners is by making a cultural icon in the region, just like what the government of Kulon Progo Regency in Yogyakarta did in June 2021. By causing the dance fragment Suroloyo Wrehaspati, it is hoped that more tourists will come to Kulon Progo Regency and consider it a unique cultural work. The research aims to compare the dance fragment Suroloyo to the traditional South Korean opera, changgeuk, both cultural icons in their regions. Some findings are found by interviewing the person in charge of the performances and literary reviews from journals, books, and internet sources. The research found that changgeuk in South Korea historically was not meant to be made as a cultural icon; it was naturally growing as a traditional culture that could be enjoyed both by locals and foreigners coming to South Korea. Meanwhile, the dance fragment Suroloyo is not yet known by the Kulon Progo people and the public. The performance was specially made by artists based on local myth, supported by the government, and purposely used as a tourist attraction. Hence, more campaigns are needed to make dance fragment Suroloyo Wrehaspati more globally recognized and bring the glory of tourism to Kulon Progo regency in Yogyakarta, Indonesia.